2015
DOI: 10.1123/jab.2014-0232
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of a Wireless Accelerometer for the Assessment of Postural Sway

Abstract: Clinicians are in need of valid and objective measures of postural sway. Accelerometers have been shown to be suitable alternatives to expensive and stationary force plates. We evaluated the test-retest reliability and balance task discrimination capability of a new wireless triaxial accelerometer (YEI 3-Space Sensor). Four testing conditions (eyes open or closed, while on a firm or compliant surface) were used to progressively challenge the static balance of 20 healthy male (n = 8) and female (n = 12) older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
2
28
2
Order By: Relevance
“…Conversely, the current study had lower reliability than the study of Saunders et al (2015), [9] who reported ICCs ranging from 0.77-0.93 for standing on a firm surface with eyes open and closed and ICCs from 0.76-0.95 for standing on foam surface. There are several possible reasons for the higher reliability in the Saunders study.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Conversely, the current study had lower reliability than the study of Saunders et al (2015), [9] who reported ICCs ranging from 0.77-0.93 for standing on a firm surface with eyes open and closed and ICCs from 0.76-0.95 for standing on foam surface. There are several possible reasons for the higher reliability in the Saunders study.…”
Section: Discussioncontrasting
confidence: 93%
“…Accelerometers are used to quantify postural sway during standing, and have been shown to have the ability to discriminate between test conditions that require different levels of postural control, between fallers and non-fallers, and young versus older adults [7][8][9]. Assessing balance by using accelerometers has been applied to different populations including people with Parkinson disease [10], stroke, children, and with community-dwelling older adults [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerometers are used to quantify postural sway during standing, and have been shown to have the ability to discriminate between test conditions that require different levels of postural control, between fallers and non-fallers, and young versus older adults [7][8][9]. Assessing balance by using accelerometers has been applied to different populations including people with Parkinson disease [10], stroke, children, and with community-dwelling older adults [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometers have quantified balance across a range of disease states and task conditions. [3][4][5][6] Accelerometers commonly mounted on the low back or sacral area have high reported correlation with force plate measures of balance. 3,7,8 Although it is acknowledged that the 2 measurement techniques measure subtly different constructs of balance (sway of center of pressure vs sacral acceleration), their relationship suggests that accelerometry offers a valid measurement method for balance.…”
mentioning
confidence: 99%